PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS IV DI SD INPRES KAKASKASEN II - Masihor, Shelomita; Reflie Lumampow, Harol; Oktavia Sumilat, Margareta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve Science and Social Studies (IPAS) learning outcomes through the implementation of the Problem Based Learning (PBL) model among fourth-grade students at SD Inpres Kakaskasen II. Based on the initial observation (pre-cycle), out of 29 students only 9 students (31%) achieved mastery learning, while 20 students (69%) had not. This research used the Classroom Action Research (CAR) method following the Stephen Kemmis and Robin McTaggart model, carried out in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through observation, interviews, tests, and documentation, and analyzed using the percentage of learning mastery with a success indicator of ≥75%. The results showed that the percentage of learning mastery reached 68.9% in Cycle I and increased to 94.8% in Cycle II, thus meeting the established success indicator. In addition, the implementation of PBL also improved students’ activeness, collaboration, and critical thinking skills. It can be concluded that the Problem Based Learning (PBL) model is effective in improving IPAS learning outcomes of fourth-grade students at SD Inpres Kakaskasen II.